1990
DOI: 10.1099/00222615-31-2-95
|View full text |Cite
|
Sign up to set email alerts
|

Protective immunity induced in mice by detoxified salmonella lipopolysaccharide

Abstract: C3H/HeNMTV mice were immunised intraperitoneally (i.p.) with lipopolysaccharide (LPS) or detoxified LPS (D-LPS) derived from Salmonella typhimurium strain SR-11. In both cases, effective protection was achieved against a challenge dose of greater than 2 x lo2 LD50 of the same organism given by i.p. injection. However, by comparison with LPS, approximately 6-to 10-fold more of D-LPS by weight was needed to protect mice to an equivalent degree. Histopathological studies showed that the initial lesions in infecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 20 publications
2
19
0
Order By: Relevance
“…Ester-linked fatty acids in lipid A may be important in this protease recognition LPS, as a derivative unable to activate the proPO system (LPSdex) has been depleted of ester-linked fatty acids (Seid & Sado#, 1981). Deacylated LPS has been shown to be up to 1000-fold less active than untreated LPS in causing Limulus amoebocyte lysate to gel (Seid & Sado#, 1981;Ding et al, 1990). These observations with deacylated LPS are similar to the lack of activation found in the P. clarkii proPO system by LPSdex reported here.…”
Section: Discussionsupporting
confidence: 77%
“…Ester-linked fatty acids in lipid A may be important in this protease recognition LPS, as a derivative unable to activate the proPO system (LPSdex) has been depleted of ester-linked fatty acids (Seid & Sado#, 1981). Deacylated LPS has been shown to be up to 1000-fold less active than untreated LPS in causing Limulus amoebocyte lysate to gel (Seid & Sado#, 1981;Ding et al, 1990). These observations with deacylated LPS are similar to the lack of activation found in the P. clarkii proPO system by LPSdex reported here.…”
Section: Discussionsupporting
confidence: 77%
“…Detoxified LPS is generated by mild alkaline hydrolysis of LPS removing the fatty acid side chains from lipid A, which are responsible for the toxic activity of LPS (41). Previous reports have indicated that LPS molecules with various deacylated forms of lipid A are capable of antagonizing biological responses to intact LPS by interacting with host cells (42,43).…”
Section: Discussionmentioning
confidence: 99%
“…However, an ideal vaccine candidate should not be limited to these immunization routes. Moreover, a general reduction of endotoxicity to minimize adverse effects might be necessary for a safe application of the OMV vaccine candidate in humans, as highlighted by a variety of other vaccine candidates containing LPS (47)(48)(49)(50)(51)(52)(53)(54)(55). For example, the Neisseria meningitidis OMV vaccines, used to control outbreaks in Scandinavia and New Zealand, include an additional step to remove most of the LPS by detergent extraction (56,57).…”
mentioning
confidence: 99%